Microbiological evaluation of bristles of frequently used toothbrushes Avaliação microbiológica das cerdas de escovas dentárias de uso frequente - Celso André Ferreira; Geovana Dagostim Savi; Ana Paula Panatto; Jaqueline da Silva Generoso; Tatiana Barichello (Dental Press Editora, 2012)
INTRODUCTION: Brushing teeth is probably the practice of oral hygiene most common in the world; however, inadequate use can become a risk to the population health, once they may be contaminated with various microorganisms. OBJECTIVE: The aim of this study was to evaluate the bacterial contamination on toothbrush bristles using different methodologies. METHOD: We used 40 toothbrushes from healthy individuals aged 3 to 58 years. The samples were grown in test tubes containing trypticase soy broth sterile, and with the help of a tracking 0.1 μl samples were placed on plates containing sheep blood agar 5% and MacConkey agar then the samples were stored in a bacteriological incubator at 37°C for 24 hours for later analysis. It was counted the colony forming units and bacteria identification present in the brush. RESULTS: On the microbiological analysis, there was a growth of Escherichia coli, Klebsiella pneumoniae, Streptococcus pyogenes and Staphylococcus coagulase negative. CONCLUSION: According to the results presented in this study, we observed a high incidence of bacterial contamination in the brushes analyzed. The most frequent microorganisms were members of the Enterobacteriaceae. The usage time of toothbrushes may be related to contamination found and, therefore, not only good hygiene ensures the reduction of microbial load, but replacing the toothbrush can also ensure individuals better oral health. INTRODUÇÃO: a escovação de dentes é, provavelmente, a prática de higiene bucal mais comumente realizada no mundo; entretanto, o acondicionamento inadequado pode se transformar em um risco para a saúde da população, uma vez que podem estar contaminadas com vários tipos de microrganismos. OBJETIVO: o objetivo desse estudo foi avaliar a contaminação bacteriana de cerdas de escovas dentais através de diferentes métodos. MÉTODOS: foram utilizadas 40 escovas de dentes provenientes de indivíduos sadios, com idade entre 3 a 58 anos. As amostras foram semeadas em tubo de ensaio contendo caldo tripticaseína de soja (TSB) estéril e, com o auxílio de uma alça de 0,1μl, as amostras foram semeadas em placas contendo ágar sangue de carneiro a 5% e ágar MacConkey. Em seguida foram armazenadas em estufa bacteriológica a 37°C por 24hs para posterior análise. Foi realizada a contagem das unidades formadora de colônias (UFC) e a identificação das bactérias presentes nas escovas. RESULTADOS: nas análises microbiológicas, houve crescimento de Escherichia coli, Klebsiella pneumoniae, Streptococcus pyogenes e Staphylococcus coagulase negativas. Conclusões: de acordo com os resultados apresentados nesse trabalho, verificamos que houve alta incidência de contaminação bacteriana nas escovas analisadas. Os microrganismos com maior frequência foram membros da família Enterobacteriaceae. O tempo de uso das escovas dentárias pode estar relacionado à contaminação encontrada e, por isso, não só uma boa higienização garantirá a redução da carga microbiana, mas a troca da escova dentária também pode garantir melhor saúde bucal aos indivíduos.